Differential Nitrogen and Water Impacts on Yield and Quality of Wheat Classes. (1st November 2019) - Bicego, Breno; Sapkota, Anish; Torrion, Jessica A.
Abstract : High wheat ( Triticum aestivum L.) grain yield and desirable quality must be considered to avoid market price penalty. Wheat classes and genotypes may respond differently to agronomic management and environmental conditions. Our goal was to characterize the yield, protein, test weight, and falling number of four hard red and four soft white spring wheat cultivars randomized within the five N levels over contrasting environments (rainfed and irrigated) in northwestern Montana. One‐third yield reduction from 2016 to 2017 was attributed to heat stress. Irrigation increased both grain yield and test weight. However, falling number was generally higher under rainfed environment, but was also cultivar dependent. 'Egan, ' 'McNeal, ' and 'Alpowa' falling number values were more resilient to environmental differences than other cultivars. Overall, soft whites had higher yields than hard reds, but with a stronger negative yield to protein relationship. Achieving high yield in hard reds via irrigation did not reduce grain protein in relation to rainfed, except at very low N (2017 control). The cultivar Egan, with Gpc‐B1 gene for higher grain protein, had similar yield to its parent material and to other hard red, though inferior to 'Vida' (characterized by extended green leaf duration after heading) under hot and dry conditions. During the less limiting year (2016), the maximum protein was achieved with much less N under irrigated environment compared with rainfed. Soft whites, due to lower grain protein requirement and lack of yield response to N in our study, can be grown with lower N input than hard reds. Core Ideas Egan ( Gpc‐B1 gene cultivar) had superior grain protein with relatively no yield penalty Vida (stay‐green trait cultivar), Alturas, and UI Stone are more resilient under varied growing conditions and management Soft white market class had higher grain yield and stronger protein dilution than hard red